Marina, Dilma e Aécio no Facebook: controvérsias e estratégias discursivas nas eleições de 2014 - Sousa, Cínthia Klumpp Martinez Magalhães (2016)
This research investigates how the candidates Marina Silva, Aécio Neves and Dilma Rousseff approached controversial themes in the digital networks during the election campaign for Brazil´s Presidency in 2014; which strategies they adopted and how their discourses reverberated among themselves. A media analysis was developed focusing on understanding the main characteristics of the digital networks, their users and the impact they had on the political scenario. The corpus of this research is composed by posts published by the candidates on their Facebook pages that were carefully selected after an intensive observation of the actors in order to identify what were the themes that generated more controversy among them. In the sequency, these posts have been analysed in an attempt to understand which discursive strategies each of the candidates has developed to build powerful discourses and to deconstruct the competitors’ candidatures. The study of the digital networks had the support of the theoris of Jamil Marques, Rafael Sampaio, Camilo Aggio and Alessandra Aldé. The selection of the corpus was supported by Bruno Latour´s researches in controversies and the discursive analysis had the support of theories of Ernesto Laclau